ChemInform Abstract: Asymmetric Transamination of α‐Keto Acids Catalyzed by Chiral Pyridoxamines. Issue 51 (5th December 2016) - Lan, Xiaoyu; Tao, Chuangan; Liu, Xuliang; Zhang, Aina; Zhao, Baoguo
Abstract: A new class of pyridoxamines bearing a side chain displays catalytic activity and promising enantioselectivities in the asymmetric transamination of α‐keto acids (I) with 2, 2‐diphenylglycine as the amine source.